Proteins : sustainable source, processing and applications - Galanakis, Charis M. (Academic Press, an imprint of Elsevier, 2019)
Proteins: Sustainable Source, Processing and Applications addresses sustainable proteins, with an emphasis on proteins of animal origin, plant-based and insect proteins, microalgal single cell proteins, extraction, production, the stability and bioengineering of proteins, food applications (e.g. encapsulation, films and coatings), consumer behavior and sustainable consumption. Written in a scientific manner to meet the needs of chemists, food scientists, technologists, new product developers and academics, this book addresses the health effects and properties of proteins, highlights sustainable sources, processes and consumption models, and analyzes the potentiality of already commercialized processes and products. This book is an integral resource that supports the current applications of proteins in the food industry, along with those that are currently under development.